A carvedilol analogue, VK‐II‐86, prevents hypokalaemia‐induced ventricular arrhythmia through novel multi‐channel effects. (4th February 2022) - Robinson, Victoria M.; Alsalahat, Izzeddin; Freeman, Sally; Antzelevitch, Charles; Barajas‐Martinez, Héctor; Venetucci, Luigi
Abstract : Background and Purpose: QT prolongation and intracellular Ca 2+ loading with diastolic Ca 2+ release via ryanodine receptors (RyR2) are the predominant mechanisms underlying hypokalaemia‐induced ventricular arrhythmia. We investigated the antiarrhythmic actions of two RyR2 inhibitors: dantrolene and VK‐II‐86, a carvedilol analogue lacking antagonist activity at β‐adrenoceptors, in hypokalaemia. Experimental Approach: Surface ECG and ventricular action potentials (APs) were recorded from whole‐heart murine Langendorff preparations. Ventricular arrhythmia incidence was compared in hearts perfused with low [K + ], and those pretreated with dantrolene or VK‐II‐86. Whole‐cell patch clamping was used in murine and canine ventricular cardiomyocytes to study effects of dantrolene and VK‐II‐86 on AP parameters in low [K + ] and effects of VK‐II‐86 on the inward rectifier current (IK1 ), late sodium current (INa_L ) and the L‐type Ca 2+ current (ICa ). Effects of VK‐II‐86 on IKr were investigated in transfected HEK‐293 cells. A fluorogenic probe quantified the effects of VK‐II‐86 on oxidative stress in hypokalaemia. Key Results: Dantrolene reduced the incidence of ventricular arrhythmias induced by low [K + ] in explanted murine hearts by 94%, whereas VK‐II‐86 prevented all arrhythmias. VK‐II‐86 prevented hypokalaemia‐induced AP prolongation and depolarization but did not alter AP parameters in normokalaemia. Hypokalaemia was associated with decreased IK1 and IKr, and increased INa‐L, and ICa . VK‐II‐86 prevented all hypokalaemia‐induced changes in ion channel activity and oxidative stress. Conclusions and Implications: VK‐II‐86 prevents hypokalaemia‐induced arrhythmogenesis by normalizing calcium homeostasis and repolarization reserve. VK‐II‐86 may provide an effective treatment in hypokalaemia and other arrhythmias caused by delayed repolarization or Ca 2+ overload.